2021
DOI: 10.1177/0895904821999838
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Expulsions, Suspensions, and Arrests on Average School Proficiency Rates in Ohio Using Fixed Effects

Abstract: Student removal became an increasingly utilized form of discipline since the implementation of zero-tolerance policies during the early 1990s. Evaluative studies have consistently found negative relationships between student removal and academic success. Majority of cases regarding student removal are for minor and non-violent offenses and literature in this field suggests that teachers’ biases and cultural misreadings widen racial disparities in school discipline and academic performance. Our study estimates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…To examine the levels of racial and socioeconomic segregation in exiters' schools, we summarized school demographics, including racial and socioeconomic composition. We also summarized math and English language arts test scores, school discipline rates (the number of suspensions per student), and stability rates (the percentage of students who remain at the school between nontransition years), as an incomplete set of factors that could be related to school quality (Lenhoff et al, 2020;Yaluma et al, 2021). We compared these characteristics of Detroit exiters' schools with the schools that suburban students attend, as well as to the Detroit exiters' choices in the city.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the levels of racial and socioeconomic segregation in exiters' schools, we summarized school demographics, including racial and socioeconomic composition. We also summarized math and English language arts test scores, school discipline rates (the number of suspensions per student), and stability rates (the percentage of students who remain at the school between nontransition years), as an incomplete set of factors that could be related to school quality (Lenhoff et al, 2020;Yaluma et al, 2021). We compared these characteristics of Detroit exiters' schools with the schools that suburban students attend, as well as to the Detroit exiters' choices in the city.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies on school discipline have largely examined out-of-school suspension due to the direct loss of learning that results from the physical removal of disruptive children from school (Wilkerson & Afacan, 2022;Yaluma et al, 2021). In-school suspension, which excludes disobedient students from classroom instruction for a short period of time but allows them to remain at school, has been comparatively understudied.…”
Section: Racial Gaps In In-school Suspensionmentioning
confidence: 99%
“…Due to this widespread implementation of school discipline policies, numerous studies have traced the existing trends in school disciplinary methods and examined their effects. Many of these studies have documented that exclusionary policies, such as in-school suspension, out-of-school suspension and expulsion, result in adverse consequences for students, such as a loss of learning, academic failure, dropouts, and eventual incarcerations (Morris & Perry, 2016;Mowen, 2017;Noltemeyer et al, 2015;Yaluma et al, 2021).…”
mentioning
confidence: 99%
“…However, to our knowledge, contemporary literature quantifying the risk of school exclusion (eg, suspensions) among autistic students is sparse and inconclusive. This lack of data is a concern because consistent evidence shows an association between school exclusion and poorer academic achievement . Early studies have shown that autistic students experienced similar or lower rates of suspension compared with their nonautistic peers; however, more recent studies have found higher rates of suspension among autistic students .…”
Section: Introductionmentioning
confidence: 99%
“…This lack of data is a concern because consistent evidence shows an association between school exclusion and poorer academic achievement. 11 Early studies have shown that autistic students experienced similar or lower rates of suspension compared with their nonautistic peers 12,13 ; however, more recent studies have found higher rates of suspension among autistic students. 14,15 Inconsistency of extant findings may be attributed to differences in data collection methods, variable sample sizes, and policy environments.…”
mentioning
confidence: 99%